Memory-Like Inflammatory Responses of Microglia to Rising Doses of LPS: Key Role of PI3Kγ - Lajqi, Trim; Lang, Guang-Ping; Haas, Fabienne; Williams, David L.; Hudalla, Hannes; Bauer, Michael; Groth, Marco; Wetzker, Reinhard; Bauer, Reinhard (Frontiers in Immunology, 2019)
Trained immunity and immune tolerance have been identified as long-term response patterns of the innate immune system. The causes of these opposing reactions remain elusive. Here we report about differential inflammatory responses of microglial cells derived from neonatal mouse brain to increasing doses of the endotoxin LPS. Prolonged priming with ultra-low LPS doses provokes trained immunity, i.e. increased production of pro-inflammatory mediators in comparison to the unprimed control. In contrast, priming with high doses of LPS induces immune tolerance implying decreased production of inflammatory mediators and pronounced release of anti-inflammatory cytokines. Investigation of the signaling processes and cell functions involved in these memory-like immune responses reveals essential role of phosphoinositide 3-kinase γ (PI3Kγ), one of the phosphoinositide 3-kinase species highly expressed in innate immune cells. Together, our data suggest profound influence of preceding contacts with pathogens on the immune response of microglia. The impact of these interactions – trained immunity or immune tolerance - appears to be shaped by pathogen dose.